NMDA receptor activity and its modulation by sulfhydryl compounds: Chemiluminescence measurements in rat brain cortical synaptosomes - (:unkn) unknown (My University, 1999)
Objective: We have used chemliuminescence (CL) measurements to investigate the effect of modulatory compounds on N-methyl-D-aspartate (NMDA) receptor activity in rat brain frontal cortex synaptosomes. Methods: Freshly prepared synaptosomes (protein concentration: 5 mg/mL) were incubated with different modulatory molecules such as Zn++ (1 mM), Cd++ (1 mM), reduced glutathione, (GSH) (1 mM, 10 mM), oxidized glutathione (GSSG) (1 mM, 5 mM), dithiothreitol (DTT) (1 mM, 10 mM) and N-ethylmaleimide (NEM) (1 mM, 10 mM) for 5 minutes at room temperature. After preincubation, 0.1 mM NMDA was added either alone or in the presence of 65 mM KCl. CL measurements were taken with lucigenin as enhancer, at 10 second intervals for 1 minute. Results: Synaptosomes showed a marked increase in CL upon addition of NMDA both in the presence and absence of KCl. When preincubated with the non-competitive NMDA receptor antagonist (Zn++) or with the calcium channel blocker (Cd++), CL formation was suppressed. DTT, a strong sulfhydryl group reducing agent, increased the activity of NMDA receptor, whereas NEM, a sulfhydryl group alkylating agent, decreased the NMDA receptor activity. Reduced and oxidized forms of glutathione decreased the receptor activity and were protective under excitotoxicity and depolarization conditions. Conclusion: Our results demonstrated that endogenous and exogenous sulfhydryl compounds affect the redox modulatory site and play important roles in the generation of reactive oxygen species after activation of the NMDA receptor.
Keywords: Chemiluminescence; Cortical synaptosomes; Excitotoxicity; NMDA receptor; Sulfhydryl group modulators